2016
DOI: 10.5173/ceju.2016.675
|View full text |Cite
|
Sign up to set email alerts
|

The detection and upgrade rates of prostate adenocarcinoma following transperineal template-guided prostate biopsy – a tertiary referral centre experience

Abstract: IntroductionWe aim to present transperineal template-guided prostate biopsy (template biopsy) outcomes at a tertiary referral centre. Furthermore, to identify the detection rate of prostate cancer in those with a previous negative transrectal ultrasound guided prostate biopsy and the upgrade rate of those on active surveillance for Gleason 3 + 3 = 6 prostate adenocarcinoma.Material and methodsWe conducted a prospective study of 200 consecutive men who underwent template biopsy over a 22-month period in a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…All of the above studies were meant to explore the anesthetic efficacy of PPB in the transrectal prostate biopsy. Owing to the high positive rate and few complications, The value of TTPB in the diagnosis of Pca is becoming more and more important [2, 3]. Hence, we evaluated the anesthetic efficacy of PPB in TTPB in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the above studies were meant to explore the anesthetic efficacy of PPB in the transrectal prostate biopsy. Owing to the high positive rate and few complications, The value of TTPB in the diagnosis of Pca is becoming more and more important [2, 3]. Hence, we evaluated the anesthetic efficacy of PPB in TTPB in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Early screening for prostate cancer (PCa) can significantly lower disease-related morbidity and even prolong life expectancy [1]. Transperineal template-guided prostate biopsy (TTPB) is one of most effective procedures for detection of prostate cancer [2, 3]. However, compared with the transrectal biopsy, transperineal route may cause more pain [4].…”
Section: Introductionmentioning
confidence: 99%
“…7 © 2022 Canadian Urological Association transrectal biopsies. 11,[16][17][19][20] Stefanova et al, reported on the results of 1,287 patients undergoing transperineal prostate biopsy in the office using local anesthesia reporting zero major complications or episodes of urosepsis. 20 Minor complications were relatively uncommon (1.9%) with temporary urinary retention representing the majority of minor complications.…”
Section: Kozel Et Al Office-based Transperineal Fusion Prostate Biopsymentioning
confidence: 99%
“…Transperineal prostate biopsies, while a small fraction of prostate biopsies performed, continue to gain traction as many centers phase out transrectal biopsies altogether in an effort to eliminate biopsy associated infection. [16][17]19 In addition, transperineal biopsy obviates the need for antibiotic prophylaxis in almost all patients, offering significant benefit in an era when antibiotic stewardship is critically important. However, perceived requirement for general above the perineum.…”
Section: Introductionmentioning
confidence: 99%
“…However, GG inconsistency accounting for upgrades still remains an important clinical issue. It is reported that only 40%-60% of prostate biopsy GGs were consistent with the final prostatectomy [ 3 10 ]. Due to the high discrepancy rate from biopsy to prostatectomy, it is urgent for physicians to predict prostate biopsy GG upgrades before surgery.…”
Section: Introductionmentioning
confidence: 99%